Literature Review : Mengidentifikasi Kesadaran Diri Individu terhadap Pengaruh Pemerasan Emosional - Erlangga Hidra; Qirani Ajeng Pinasti; Supriyono (FKIP, Universitas Palangka Raya, 2025)
Emotional Blackmail is a powerful form of manipulation where people closest to us threaten, either directly or indirectly, with the aim of making us feel guilty and making us anxious if we don't do what they want. Emotional blackmail is a concept presented by psychologist Susan Forward in the book